2018
DOI: 10.1007/s12032-018-1176-6
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility of real-world patients with chemo-refractory, K-RAS wild-type, metastatic colorectal cancer for palliative intent regorafenib monotherapy

Abstract: The CORRECT trial demonstrated survival benefits with regorafenib monotherapy in patients with treatment-refractory, metastatic colorectal cancer (mCRC). However, the trial's stringent eligibility criteria for regorafenib may limit its external validity. We aimed to examine treatment attrition rates and eligibility for regorafenib in routine practice. We identified patients at the British Columbia Cancer Agency diagnosed with mCRC who demonstrated disease progression or intolerable toxicity on 2 or more lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This compares favorably with similar reported studies. 13,15 Our subgroup analysis confirmed that performance status is one of the most important factors in regorafenib efficacy. All prior pivotal studies included only patients with PS 0 to 1, while one-third of our patients had PS more than one with a significant difference in PFS and OS (P = .0002 and .01, respectively) on both univariate analysis and multivariate analysis (P = .0097 and .0065, respectively).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This compares favorably with similar reported studies. 13,15 Our subgroup analysis confirmed that performance status is one of the most important factors in regorafenib efficacy. All prior pivotal studies included only patients with PS 0 to 1, while one-third of our patients had PS more than one with a significant difference in PFS and OS (P = .0002 and .01, respectively) on both univariate analysis and multivariate analysis (P = .0097 and .0065, respectively).…”
Section: Discussionsupporting
confidence: 69%
“…This result is in concordance with the result of the REBACCA study where 10.6% of patients had PS more than 1 and the difference in OS between the groups with PS 0 to 1 compared to >1 was statistically significant ( P < .001). 16 In addition, performance status was reported to correlate with outcome in the study reported by Angeles et al 15…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main indication described in its drug insert (Merck, Germany) is mCRC which is resistant to chemotherapy with irinotecan-based drugs. Previous studies have found that mCRC is often accompanied with genetic mutations, such as K-Ras mutations, and the mutated mCRC is no longer regulated by EGFR (14,15). At this point, the drugs that target EGFR will become ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al (26). Additionally, Qin et al(22) and Angeles et al(14) obtained a positive result through RCT, suggesting that the use of cetuximab can be benefit to mCRC patients, while RCT conducted by Yu et al(19), Sirotnak et al(11) came to a contrary conclusion. Therefore, there is no consensus on the effective therapeutic significance of cetuximab in mCRC patients with ITT.…”
mentioning
confidence: 99%